Northern exposure: a comparison study of Alaska and Yukon models of measuring community wellbeing - Spiers, Kent (My University, 2015)
The main objective of this study is to examine models of measuring community wellbeing in Alaska and Yukon to determine if they were developed with the input of residents and if these models reflect local living conditions. Research suggests communities that establish an agreed upon model of measuring community wellbeing will benefit by having an increase in public involvement in local decision-making, and larger capture of material wealth and empowerment over resource management (Varghese et al. 2006). A core problem is that while many communities have started to develop ways to evaluate wellbeing, there is a lack of research on the various models in the Arctic. There are several unique challenges to developing a model in Arctic communities such as the clash between mainstream and Indigenous definitions of wellbeing, the lack of data and small population sizes (Taylor 2008 & Bobbitt et al. 2005). For this study I conducted an in-depth search for publically available models in Alaska and Yukon and conducted semi-structured interviews with experts. Part one of the analysis was searching through records of each model to document community outreach methods, part two was an experimental content analysis to identify themes across models in both regions, and part three was a content analysis of the interviews. I did not find any significant difference in the design frame, content or consultation with local residents between the models in Alaska and Yukon.
Keywords: Community wellbeing; Models of measuring community wellbeing in Alaska and Yukon; Community input; Mainstream and Indigenous definitions of wellbeing